Peran HIMPAUDI Dalam Pengembangan PAUD - JM Tedjawati (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
The purpose of this writing an article is to obtain data and information about the role of HIMPAUDI in the implementation of Early Chilhood Development (ECD), expecially to: 1) promote the importance of qualified ECD; 2) conduct training and organizational development in stages, 3) accommodate, promote and realize the aspirations of educators and early age (AUD) child care staff, and 4) facilitate professional development of educators and early childhood education personnel. The findings of this analysis are: 1) the role of HIMPAUDI in socializing early childhood programs done through various ways namely for AUD activities (such as dancing, singing along, gymnastics), seminars on improving the quality of early childhood institutions, and provide guidance about the requirements to be met in establishing early childhood institutions; 2) in the organization training and development, HIMPAUDI has made the establishment of HIMPAUDI management in provincial, district and subdistrict level; 3) HIMPAUDI has struggled for educators to get the incentives, both received from the government and businesses developed by HIMPAUDI; and 4) HIMPAUDI role in the development of AUD professional teachers and staff has been realized through: (i) the opening of S1 programs in college; (ii) basic training for AUD educators, training of PAUD concept and AUD learning approach, (iii) Training on online data management for HIMPAUDI management, and (iv) seminars about the thematic pattern of early childhood learning.Â ABSTRAKÂ Tujuan dari tulisan ini adalah untuk memperoleh data dan informasi tentang peran Himpunan Pendidik dan Tenaga Kependidikan Anak Usia Dini Indonesia (HIMPAUDI) dalam pelaksanaan PAUD, khususnya dalam hal: 1) Mensosialisasikan pentingnya PAUD yang berkualitas; 2) Melakukan pembinaan dan pengembangan organisasi secara berjenjang; 3) Menampung, memperjuangkan dan mewujudkan aspirasi para pendidik dan tenaga kependidikan Anak Usia Dini (AUD); dan 4) Memfasilitasi pengembangan profesi pendidik dan tenaga kependidikan anak usia dini. Temuan analisis tulisan ini yaitu: 1) Peran HIMPAUDI dalam mensosialisasikan program PAUD dilakukan melalui berbagai cara yaitu kegiatan bagi AUD antara lain seminar peningkatan kualitas lembaga PAUD, dan memberikan pengarahan akan persyaratan pendirian yang harus dipenuhi oleh lembaga PAUD; 2) Dalam pembinaan dan pengembangan organisasi, HIMPAUDI telah dilakukan pembentukan pengurus HIMPAUDI dari tingkat provinsi, kabupaten/kota sampai tingkat kecamatan; 3) HIMPAUDI telah memperjuangkan para pendidik untuk memperoleh insentif, baik yang diterima dari Pemerintah maupun usaha yang dikembangkan oleh HIMPAUDI; dan 4) Peran HIMPAUDI dalam pengembangan profesi pendidik dan tenaga kependidikan AUD telah diwujudkan melalui: (i) Pembukaan program S1 di perguruan tinggi; (ii) Pelatihan dasar bagi pendidik AUD, pelatihan konsep PAUD dan pendekatan pembelajaran AUD; (iii) Pelatihan pengelolaan data online bagi pengurus HIMPAUDI; dan (iv) Seminar pola pembelajaran tematik pada PAUD.